Gramática e erótica da percepção na psicanálise - Menéndez, Ada Jimena García (Universidade Federal de São Carlos, 2011)
The purpose of this thesis is to demonstrate the existence of an original psychoanalytical theory of perception, a theory which subverts philosophical and psychological traditional conceptions on the matter. In order to establish and characterize this doctrine of perception not explicit in Freud s works our methodology proposes rereading Freudian texts in the light of philosophy and different schools of the psychoanalytical movement. This work follows a path that leads from an archeology of Freudian metapsychology one that enables to sketch the grammar of perception to state the intrinsically pulsional dimension of the perceptive process. As regards the grammar of perception, Freud follows a tradition that links perception to the material aspects of the trace, especially with the fundamental notion of mnemic trace . From the beginning of his work, perception is approached as related to the gramma, the letter, the character of writing. Nevertheless, the rules of this psychoanalytical grammar are particular, paradoxical, drawn on the horizon of loss and plural times, oriented by a deferred action (Nachträglichkeit). Perception is anchored in a negative dimension. As regards the erotics of perception, the true revolution of the analytical doctrine of perception consists in revealing that perception is not absolutely dependant on physiology: it is overturned, perverted, by the logics of desire. Perception is thus found at the course of this intersection, on a hybrid spot between the grammar of the image and the word and a dimension beyond them, which is erotic, pulsional.
Keywords: Filosofia; Epistemologia; Filosofia - representação; Alucinação; Filosofia irrepresentável; Pulsão; CIENCIAS HUMANAS::FILOSOFIA